ACCUMULATION OF GLOBAL SOLAR RADIATION FOR THE PRODUCTION OF SEEDLINGS OF Cordia americana UNDER DIFFERENT MANAGEMENTS - Trautenmüller, J. W.; Borella, J.; Lambrecht, F. R.; Valerius, J.; Costa Júnior, S. (Revista Brasileira de Engenharia de Biossistemas, 2016)
The plant growth depends on the balance of accumulated biomass through photosynthesis. Thus, biomass production has to be a conversion efficiency of the intercepted function of photosynthetically active radiation (RFAi) for photoassimilates, varying according to the conditions under which plants are grown. This study aimed to quantify the incidence of solar radiation for the production of Cordia americana seedlings subjected to different sized tubes and plant densities. Therefore, an experiment was conducted in randomized block design at random, to study the production of seedlings in two tubes sizes: large (TG) and medium (TM), and two plant densities in the tray, high (DA) 100% of the tray and average occupancy (DM), 50% which were determined RFAi, global solar radiation and total dry biomass of seedlings. It has been found that are required 1590.5, 1607.1, 2135.4 and 2094.5 MJ.m-2 for the production of standard American Cordia seedlings for treatments TGDA, TGDM, TMDA and TMDM, respectively.